1985
DOI: 10.1007/bf00451904
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccination and immune response in children with malignant diseases

Abstract: Fifty children with malignant diseases were vaccinated against hepatitis B. Twenty-nine children suffered from leukaemia or non-Hodgkin's lymphoma; 14 of these were on intensive chemotherapy (group I) and 15 were without intensive therapy (group II). The other 21 children had various forms of solid tumours, 14 of them were on intensive therapy (group III) and 7 were without intensive therapy (group IV). To evaluate the immune response, we determined antibody titres over a period of more than 14 weeks after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

1987
1987
2000
2000

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…HBV vaccination of these seronegative patients at diagnosis may be recommended [1]. The seroconversion rate following three double doses of vaccine administered at monthly intervals was reported to be 19-41% in children with solid tumors [12,13]. We have also obtained a seroconversion rate of 40% in 25 children with solid tumors (unpublished results).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…HBV vaccination of these seronegative patients at diagnosis may be recommended [1]. The seroconversion rate following three double doses of vaccine administered at monthly intervals was reported to be 19-41% in children with solid tumors [12,13]. We have also obtained a seroconversion rate of 40% in 25 children with solid tumors (unpublished results).…”
Section: Discussionmentioning
confidence: 57%
“…We have also obtained a seroconversion rate of 40% in 25 children with solid tumors (unpublished results). In several studies, the best seroconversion rates were obtained in patients who do not receive intensive chemotherapy [12,13]. As antineoplastic therapy intensity increases, the antibody response to chemotherapy decreases.…”
Section: Discussionmentioning
confidence: 96%
“…This might also cause more immunosuppression in them. Previous studies demonstrated impaired immune response to active vaccination in children with leukemia during intensive chemotherapy [9,10]. Therefore, in our study, children with leukemia had active vaccination after completing the intensive chemotherapy period which might secure a better immune response.…”
Section: Discussionmentioning
confidence: 86%
“…Despite donor screening for hepatitis B, acute and chronic hepatitits B remains a problem on paediatric oncology wards [5,19]. In addition, evidence of chronic non-A-non-B (NANB) hepatitis is found in a significiant proportion of paediatric cancer patients [13,15].…”
Section: Introductionmentioning
confidence: 99%